2011
DOI: 10.1061/(asce)co.1943-7862.0000343
|View full text |Cite
|
Sign up to set email alerts
|

Neural Network–Based Intelligent Compaction Analyzer for Estimating Compaction Quality of Hot Asphalt Mixes

Abstract: The development and validation of a tool that can estimate the level of compaction of a Hot Mix Asphalt (HMA) pavement during its construction is addressed in this paper. Densification of asphalt pavements during their construction is usually accomplished through the use of vibratory compactors. During compaction, the compactor and the asphalt mat form a coupled system whose dynamics are influenced by the changing stiffness of the mat. In this paper, it is shown that the measured vibrations of the compactor al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…It is believed that the thin asphalt overlays being compacted could hinder the IC roller from using its intelligent features of applying more compactive effort when needed (9). Commuri et al developed a neural network-based intelligent asphalt compaction analyzer (IACA) to estimate the level of compaction in the field by using a steel vibratory compactor (10). Commuri et al reported that density measured with the IACA correlated well with the field cores' densities (10).…”
Section: Comprehensive Evaluation Of Compaction Of Asphalt Pavements mentioning
confidence: 99%
“…It is believed that the thin asphalt overlays being compacted could hinder the IC roller from using its intelligent features of applying more compactive effort when needed (9). Commuri et al developed a neural network-based intelligent asphalt compaction analyzer (IACA) to estimate the level of compaction in the field by using a steel vibratory compactor (10). Commuri et al reported that density measured with the IACA correlated well with the field cores' densities (10).…”
Section: Comprehensive Evaluation Of Compaction Of Asphalt Pavements mentioning
confidence: 99%
“…Other studies confirmed that the stiffness of the underlying layer has a great impact on the IC stiffness measurements of the asphalt layer being compacted [11]. Commuri et al [12] developed a neural network-based Intelligent Asphalt Compaction Analyzer (IACA) to estimate the compaction quality of asphalt pavements. The results showed that density measured using the IACA method correlated well with the density in the field.…”
Section: Overviewmentioning
confidence: 96%
“…Recently, Intelligent Compaction (IC) technology was used to monitor the field compaction of asphalt pavements in real time [10][11][12]. There are several IC systems that are used and commercially available [13][14][15][16][17][18].…”
Section: Overviewmentioning
confidence: 99%
“…The stiffness measured using the IC roller is influenced by the stiffness of the materials underneath (Asphalt Institute 2010). Commuri et al (2011) developed a neural network-based intelligent asphalt compaction analyser (IACA) to quantify the compaction of asphalt mixtures in the field. They reported good correlation between density measured using the IACA and density in the field.…”
Section: Introductionmentioning
confidence: 99%